If it's not what You are looking for type in the equation solver your own equation and let us solve it.
56x+(-5x+9x)=0
We simplify the equation to the form, which is simple to understand
56x+(-5x+9x)=0
Simplifying terms in parentheses
56x+(+4x)=0
Remove unnecessary parentheses
+56x+4x=0
We move all terms containing x to the left and all other terms to the right.
+56x+4x=0
We simplify left and right side of the equation.
+60x=0
We divide both sides of the equation by 60 to get x.
x=0
| -1-2x=3 | | 4(2a+-1)+5(4+-2a)-3a=-4(5+2a)-4 | | 0.41=0.07x | | -14=x+22 | | 0.41=0.07 | | x-8.8=-3.3 | | 0.44=0.07x | | 0.27=0.07x | | 0.21=0.07x | | y-24=-5 | | 2x^2+12x=110 | | 9(y-3)=42 | | 3x-4y=x-3y | | 2x+12= | | 2x-10=x+84 | | 16-8y=-80+4y | | 2*2+6= | | 7x=3(4x-5) | | -5u+19=-2(u+1) | | 4(v+9)=7v+45 | | w^2-3w-220=0 | | 2w+34=-2(w-7) | | -14=-2y+4(y-3) | | 9-3x=x-3 | | 27=-7u+4(u+3) | | -4w+7(w-7)=-28 | | -8=2(v+6)+3v | | -7x+3(x-4)=-4 | | 3(y+6)+5y=34 | | -4(x+3)+4(2x+5)=16 | | 9+5(2x-3)=34 | | 16(3)-2= |